2020
DOI: 10.15804/tner.20.61.3.09
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hybrid Task-Based Language Teaching and Critical Thinking on Writing Performance in Indonesia

Abstract: Th is study aims to describe the eff ect of hybrid task-based language teaching and critical thinking skills on writing performance among Indonesian learners. Th is study employed experimental research with a factorial design. Th e participants were Indonesian undergraduate learners majoring in an English program. Th e instruments used were critical thinking questionnaires and writing tests in the genre-based writing course. Th e results of the study showed that hybridtask-based language teaching was eff ectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
0
2
1
Order By: Relevance
“…There is a significant positive correlation between the five factors in the BL environment, except for no direct relationship between the rules and division of labor factors. Unlike previous research [ 6 , 39 , 87 , 88 ] indicating that BL positively impacts EFL writing performance, the results of this study suggest that BL positively influences writing performance through different factors to different extents.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There is a significant positive correlation between the five factors in the BL environment, except for no direct relationship between the rules and division of labor factors. Unlike previous research [ 6 , 39 , 87 , 88 ] indicating that BL positively impacts EFL writing performance, the results of this study suggest that BL positively influences writing performance through different factors to different extents.…”
Section: Discussioncontrasting
confidence: 99%
“…the five factors in the BL environment, except for no direct relationship between the rules and division of labor factors. Unlike previous research [6,39,87,88] indicating that BL positively impacts EFL writing performance, the results of this study suggest that BL positively influences writing performance through different factors to different extents. The present study found the most significant correlation between the subject factor and EFL writing performance, implying that EFL students are the most crucial element in EFL writing improvement in BL contexts.…”
Section: Plos Onecontrasting
confidence: 99%
“…Kompetensi berpikir kritis dan pemecahan masalah merupakan salah satu kompetensi yang dibutuhkan di era 21 tahun ini kompetensi kreativitas, komunikasi, dan kolaborasi (Wikanengsih, 2020). Beberapa penelitian yang sudah dilakukan menyatakan bahwa penelitian berpikir kritis sangat mampu untuk meningkatkan kegiatan pembelajaran bahasa di Perguruan Tinggi salah satunya penelitian (Tusino, 2020) Hasil penelitian menunjukkan bahwa pengajaran bahasa berbasis tugas hibrida efektif untuk meningkatkan kinerja menulis siswa EFL. Hasil penelitian menunjukkan bahwa 22 sub-indikator berpikir kritis siswa ditemukan kesamaan jenis kelamin dan 20 sub-indikator juga ditemukan kesamaan dalam kelompok pengetahuan.…”
Section: Landasan Ontologi Bahasaunclassified